2014
DOI: 10.1371/journal.pone.0092125
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alpha-1 and Alpha-2 Adrenoceptors in Restraint Stress-Induced Liver Injury in Mice

Abstract: Acute stress affects cellular integrity in many tissues including the liver, but its underlying mechanism is still unclear. The aim of the present study was to investigate the potential involvement of catecholamines and adrenoceptors in the regulation of acute restraint stress-induced liver injury. Restraint was achieved by placing mice in restraint tubes. Mice were treated with either an α-l antagonist, prazosin, an α-2 antagonist, yohimbine, a β-l antagonist, betaxolol, a β-2 antagonist, ICI 118551, or a cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 42 publications
(47 reference statements)
3
26
0
4
Order By: Relevance
“…In this study, exposure of rats to acute CRS has resulted in hepatic damage and inflammation that was confirmed by histological examination. Zhu et al () reported that exacerbation in oxidative stress can be the result of not only an increase in ROS but also due to decrease in antioxidant capacity, which is in agreement with results of this study, as acute CRS has resulted in significant increase in hepatic MDA and decrease in TAC levels that is also as found by Dekanski et al ().…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, exposure of rats to acute CRS has resulted in hepatic damage and inflammation that was confirmed by histological examination. Zhu et al () reported that exacerbation in oxidative stress can be the result of not only an increase in ROS but also due to decrease in antioxidant capacity, which is in agreement with results of this study, as acute CRS has resulted in significant increase in hepatic MDA and decrease in TAC levels that is also as found by Dekanski et al ().…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that the expression of caspase‐3 was significantly increased in acute CRS group as compared with either control or omega‐3 group that is as found by Zhu et al () and Fayez, Awad, El‐Naa, Kenawy, and El‐Sayed (). Zhang, Li, Han, and Shi () stated that the induced activation of caspases results in upregulation of caspase‐9 and caspase‐3 and leads to dysfunction of mitochondria that in turn promotes the apoptotic process.…”
Section: Discussionsupporting
confidence: 88%
“…In response to stress condition, pro-apoptotic (BAX) and anti-apoptotic (Bcl-2) proteins regulate the release of cytochrome c from the outer mitochondrial membrane, which activates caspases and thus triggers apoptosis (Kubera, et al, 2011). It has been shown that restraint stress causes cellular apoptosis through activation of caspases-9 and −3 and increase in the BAX/Bcl-2 ratio (Zhu et al, 2014). In our study, sub-chronic restraint stress for 5 days produced a pro-apoptotic response, as evidenced by increased BAX/Bcl-2 ratio and elevated caspase-9 and caspase-3 activities in the PFC and HIP.…”
Section: Discussionmentioning
confidence: 99%
“…Stress is an integral component of human life and is considered as any condition that leads to perturbation of the body's homeostasis [11]. During extreme stress situations, the homeostatic mechanisms of the organism become deficient and the survival of the organism is thereby threatened.…”
Section: Discussionmentioning
confidence: 99%